Entitlements according to the Shafi’i School and their Impact on Contracts and Transactions: An Applied Fundamental Study - Bahmeed, Qais H. A.; Al-Babeli , Manal A.; Al-Froukh , Khaled A. (Dirasat: Shari’a and Law Sciences, 2023)
Objectives: This study aims to clarify the concept of entitlement in the Shafi’i School and how it is transmitted among people through "disclaiming responsibility," which is considered a legitimate solution for obtaining what does not fall into one’s possession by buying and selling for legal reasons that prevent this. Methods: The study employed a descriptive approach to define legal terminology and an inductive and transfer approach relying on the sayings of the jurists in the Shafi’i School. It examined the concept of entitlement and its transmission and exchange between people, shedding light on its effects on contracts and transactions. The study also used the analytical method to explain the reasons for entitlement and its types according to the Shafi’i Madhab, and presented its modern implementation. Results: The study of Shafi’i jurisprudence shows that entitlement entails distinctive connotations, some of which allow a beneficiary to solely use it without any competition, while other varieties of entitlement enable a person to own a place or enjoy a certain benefit without being allowed to either buy or sell it. Conclusions: The study recommends that entitlement has a unique treatment in the Shafi’I School. It also stresses the notion that entitlement cannot be legalized or proliferated among people, as it is conducted via a semi-purchasing process through “disclaiming responsibility.” The study suggests that someone may fully grant entitlement to others after death, unlike property which should be distributed fairly after death.